Perbedaan kadar ureum, natrium, kalium dan klorida pra dan pasca hemodialisa pada pasien dengan penyakit ginjal kronik - Syaiful Anwar; Ariosta Ariosta (DiscoverSys Inc., 2019)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible damage to kidney function (GFR < 60 ml / minute / 1.73 m2). The function of the kidneys is to maintain stability, electrolyte level, osmolarity of extracellular fluid and excrete products such as urea, uric acid, and creatinine. CKD disrupts electrolyte fluid balance and uremia, thus requiring renal replacement therapy in the form of dialysis or kidney transplantation. Different levels of urea, sodium, potassium, and chloride pre- and post-hemodialysis can be a consideration for the management of hemodialysis in CKD patients. This study aimed to determine the difference in urea, sodium, potassium, and chloride pre- and post-hemodialysis in CKD patients.Method: This was a cross-sectional analytical observational study of pre- and post hemodialysis conducted from September to October 2018. Normally distributed data were analyzed using the paired t-test, while data that were not normally distributed were analyzed using the Wilcoxon test. It was considered significant when the p-value was < 0.05.Results: There was a total of 50 patients consisting of 30 males (60.0%) and 20 females (40.0%). The mean age of the patients was 51.10 ± 7.48 years. The level of pre-hemodialysis urea (161.96 ± 53.80 mg / dL) was significantly different from post-hemodialysis (120.70 ± 40.84 mg / dL). The level of pre-hemodialysis sodium (134.5 mmol / L) was significantly different from post-hemodialysis (140 mmol / L). The level of pre-hemodialysis potassium (5.6 mmol / L) was significantly different from post-hemodialysis (4.6 mmol / L). The level of pre-hemodialysis chloride (100 mmol / L) was significantly different from post-hemodialysis (96 mmol / L). Conclusion: There was a significant difference in urea, sodium, potassium, and chloride between pre- and post-hemodialysis (p < 0.05).